TRUTH IN ANGLO-AMERICAN PROVERBS - Petrova, Roumyana (Proverbium - Yearbook, 2019)
This study explores the notion of truth stored in a large cor-pus of Anglo-American old and contemporary proverbs. It demonstrates the potential of the theory of the cultureme as a research tool in linguoculturological studies. The application of this theory helps reveal a rich, unique, complex and multifaceted notion of truth, which is the fifth key cultural constant characterizing the American identity (after the transcendent (God), society and the world, the human being, and nature).